JANGAN SEBUT ITU “BATIK PRINTING” KARENA BATIK BUKAN PRINTING - Embran Nawawi (Melayu Arts and Performance Journal, 2018)
ABSTRACT Batik is a culture in the history that proceeds in accordance with its civilization. Batik is a cultural history then becoming a world culture that want to be owned by many new civilizations. If Batik can be explained with the various basis of knowledge, then batik is a science in which there is special technique and process; Batik is Literature in which there are many stories, mantras, and beautiful prayers; Batik is a creativity which its every design is present individually; and Batik is an economy which is a clothing commodity plus art in one package. However Batik is not a printing, because Batik is a technique and process that together in it there is a motif/pattern with the produced artistic value and economic value. Therfore Batik should be seen in the form of  historical science (History), in the form of Arts and Creativity, even in the form of an unique marketing science. Keywords: batik, printing, printing batik, not batik, not printing  ABSTRAK Batik adalah sebuah budaya dalam sejarah yang masih berjalan sesuai dengan peradabannya. Batik adalah sebuah sejarah budaya yang mejadi budaya dunia yang ingin dimiliki banyak peradaban baru. jika Batik itu dapat dijelaskan dengan berbagai dasar ilmu, maka batik adalah sebuah Ilmu Pengetahuan yang di dalamnya terdapat teknik dan proses yang khusus, Batik adalah Sastra yang di dalam nya banyak kisah, mantra dan, doa yang indah, Batik adalah Kreatifitas yang setiap rancangannya hadir secara individual, dan Batik adalah perekonomian yang merupakan komoditi sandang dengan seni dalam satu kemasan. Tetapi batik bukan printing, karena Batik adalah sebuah teknik dan proses yang bersama di dalam nya ada motif /  pola dengan nilai seni yang dihasilkan, dan bernilai ekononi. Jadi batik seharus nya kita lihat dalam bentuk ilmu Sejarah, dalam bentuk Ilmu Seni dan Kreatifitas, bahkan dalam bentuk ilmu pemasaran yang unik.